Young children's ability to make predictions about novel illnesses. Issue 5 (31st August 2021) - DeJesus, Jasmine M.; Venkatesh, Shruthi; Kinzler, Katherine D.
Abstract: Understanding disease transmission is a complex problem highlighted by the COVID‐19 pandemic. These studies test whether 3‐ to 6‐year‐old children in the United States use information about social interactions to predict disease transmission. Before and during COVID‐19, children predicted illness would spread through close interactions. Older children outperformed younger children with no associations between task performance and pandemic experience. Children did not predict that being hungry or tired would similarly spread through close interactions. Participants include 196 three‐ to six‐year‐olds (53% girls, 47% boys; 68% White, 9% Black, 7% Asian, 6% Hispanic or Latinx), with medium‐sized effects ( d  = .6, η p 2  = .3). These findings suggest that thinking about social interaction supports young children's predictions about illness, with noted limitations regarding children's real‐world avoidance of disease‐spreading behaviors.